COMPETITIVENESS OF SLOVAK POWER PLANTS IN CONNECTION WITH GLOBAL CHANGES IN THE DEVELOPMENT OF ELECTRIC ENERGY PRICES - Štofová, Lenka; Szaryszová, Petra; Vajdová, Jana (Journal of Applied Engineering Science, 2023)
A cost framework we applied to provide an overview of bioenergy issues related to the process with renewable fuels and focuses on several possible profitability scenarios and the future development of Slovak power plants in a competitive electricity market. The aim of the paper is to propose alternative scenarios and forecast the development of Slovak power plants. The economic benefits of transitioning to alternative biofuel were analysed within the research in cooperation with the Vojany Black Coal Power Plant (EVO). To confirm the most economically efficient types of fuels used in the combustion process was used Data Envelopment analysis (DEA). Within the methodology used were also identified the factors influencing the price of electric energy (EE) on the market and subsequently the profitability of power plants. Scenarios for the future development of EE prices were identified using the statistical method FORECAST.FUNCTION. Despite the predicted increase in the market price of EE we conclude that the use of co-combustion fuels is socially beneficial compared to the use of biofuels under a wide range of assumptions regarding technical, economic and environmental characteristics. The relationship and extent of influence between coal, emission allowance and oil prices, determining EE prices were quantified by regression analysis and Analysis of Variances (ANOVA). The paper contains current data from available databases and market forecasts and the absence of analyses for economic development, sustainability, and competitiveness of Slovak power plants in the unfavourable period of the ongoing COVID-19 pandemic and war conflict Russia-Ukraine.
Keywords: merit order principle, electric energy, combustion process, sustainability, competitiveness